Strength determination of rocks by using indentation tests with a spherical indenter. (May 2017) - Kitamura, Manami; Hirose, Takehiro
Abstract: We conducted spherical indentation and uniaxial compression tests on four rock types of various porosities (<20%). For both methods, the compressive strength increased with decreasing porosity, but the strength obtained by the uniaxial compression test ( C o ) was lower than that obtained by the indentation test ( C i ). We established a linear relationship between C o and C i, expressed by C o = 0.513 × C i . The difference in strength obtained by the two methods might reflect a considerable amount of inelastic deformation due to pore collapse under the indenter, and the lack during indentation testing of the lateral deformation characteristic of uniaxial compression. The empirical relationship between the two methods will allow conversion of the results of indentation tests to values equivalent to those obtained from uniaxial compression tests. We applied the method to drill-cuttings retrieved from the Nankai accretionary prism during Integrated Ocean Drilling Program Expedition 348. The C o –porosity relationship of the cuttings determined by the indentation tests was consistent with the previously reported relationships obtained from cylindrical specimens by using conventional compression experiments. The method can be used to characterize the mechanical behavior of rocks by obtaining data from smaller specimens than those required for conventional rock deformation experiments. Highlights: A correlation between indentation and uniaxial compressive strength was confirmed. Uniaxial compressive strength is estimated by indentation test on small rock chip. An indentation technique to measure mechanical property of rocks is developed.